Hydrological connections in a glaciated Andean catchment under permafrost conditions (33°S) - S. Ruiz Pereira; B. Díez; J. Cifuentes-Anticevic; S. Leray; F. Fernandoy; C. Marquardt; F. Lambert (Journal of Hydrology: Regional Studies, 2023)
Fresh water supply is critical along the Andes, where drought conditions over the past decade are projected to persist. At high Andean headwater catchments, frozen ground conditions are assumed to modulate groundwater flow paths and their hydrological signals at different timescales. However, knowledge of hydrological connections in subtropical Andean catchments is still very sparse. This study assessed hydrological connections and their impacts on groundwater contribution to baseflow in a headwater proglacial aquifer located in central Chile at 33° S and 3600 m a.s.l. We collected and analyzed snow, glacial stream, and groundwater spring water samples between 2019 and 2021. We combined of water isotope and metagenomic proxies with the hydraulic parameterization of the catchment to deliver mean transit time distributions through the proglacial aquifer. The new hydrological insights for the region include the finding that groundwater spring signals delivered sub-decadal transit times, implying likely origins from glacial or interstitial ice. Additionally, the stable isotope signature showed that groundwater consistently differs from snow and surface runoff. The 16S rRNA metabarcoding analyses demonstrated the presence of psychrophilic microorganisms in groundwater springs, supporting the idea of a late warm-season activation of interstitial ice due to thawing events associated with a differential relative-abundance of specific cryophilic bacteria. Finally, our results suggest hydrological connections and dampening timeframes between glaciers, proglacial areas, and groundwater springs, most likely from thawing sources.